LncRNA PLAC2 upregulates miR-663 to downregulate TGF-β1 and suppress bladder cancer cell migration and invasion - Zhang, Zhenxing (BMC Urol, 2020)
BACKGROUND: The roles of lncRNA PLAC2 in bladder cancer (BC) were explored. METHODS: The expression of PLAC2 in two types of tissue of BC patients was detected by RT-qPCR and the expression data were compared by paired t test. The 56 patients were staged according to the AJCC criteria, and 12, 15, 15 and 14 cases were classified into stage I-IV, respectively. The expression of TGF-β1 and miR-663 in BC tissues were also detected by RT-qPCR experiments. RESULTS: Our data showed that the expression levels of PLAC2 were significantly lower in BC tissues than that in non-cancer tissues. The expression of PLAC2 was not affect by clinical stages and low expression levels of PLAC2 predicted lower survival rate. The expression of PLAC2 was positively correlated with miR-663 and inversely correlated with TGF-β1 in BC tissues. In BC cells, downregulated TGF-β1 and upregulated miR-663 were observed after the overexpression of PLAC2. Overexpression of PLAC2 also resulted in suppressed invasion and migration of BC cells. Overexpression of miR-663 resulted in downregulated TGF-β1 but did not affect the expression of PLAC2. Overexpression of TGF-β1 reduced the inhibitory effects of overexpression of PLAC2 and miR-663 on cell migration and invasion. CONCLUSION: PLAC2 can upregulate miR-663 to downregulate TGF-β1 and suppress BC cell migration and invasion.